Dysregulation of Tissue Factor, Thrombin-Activatable Fibrinolysis Inhibitor, and Fibrinogen in Patients Undergoing Total Joint Arthroplasty. (November 2017) - Wanderling, Christopher; Liles, Jeffrey; Finkler, Elissa; Carlsgaard, Peter; Hopkinson, William; Guler, Nil; Hoppensteadt, Debra; Fareed, Jawed
Total joint arthroplasty (TJA) of the hip or knee (THA, TKA) has become an increasingly common procedure. While TJA is a successful treatment for individuals experiencing degenerative joint diseases, it is well known that one of the most common perioperative complications of TJA is deep venous thrombosis (DVT). To profile tissue factor (TF), microparticle-tissue factor (MP-TF), thrombin-activatable fibrinolysis inhibitor (TAFI), and fibrinogen levels in patients undergoing TJA to determine potential preexisting Hemostatic dysregulation. De-identified blood samples were obtained from patients undergoing TJA 1 day pre- and 1 day postprocedure. Plasma samples were analyzed using enzyme-linked immunosorbent assay kits for fibrinogen, TAFI, TF, and MP-TF; fibrinogen levels were also assessed using a clot-based activity assay. In comparison with healthy controls, there were significant increases of fibrinogen and MP-TF levels, while there were significant decreases in TF and TAFI levels in the preoperative and postoperative patients. Comparing the pre versus postoperative patients, no significant differences were found; interestingly, however, surgical intervention exacerbated the changes found in the preoperative samples compared to the controls. The results of this study confirm that patients undergoing TJA have preexisting alterations in the fibrinolytic system. Surgical intervention tended to exacerbate these changes. The alterations observed in this study may provide insight as to why TJA is associated with higher rates of DVT and thromboembolism.